An acryl resin-based swellable microneedles for controlled release intradermal delivery of granisetron. (4th May 2018) - Yang, Guozhong; He, Meilin; Zhang, Suohui; Wu, Man; Gao, Yunhua
Abstract: Swellable microneedles (SMNs) are made of hydrogels and can deliver drug with controlled delivery rate by the cross-link density of the hydrogel. In this study, an acryl resin-based SMNs was developed for poorly water-soluble drugs. The making process of the SMNs is very simple and only need 60 min. The SMNs has high mechanical strength and is not easily broken. In-vitro release of SMNs-loaded model drug, granisetron base (GRB), was investigated. The results showed that seven days controlled release of GRB was obtained when SMNs contained pore-foaming agents (1.5% dicalcium phosphate (CaHPO4 ) and 1.5% polyvinylpyrrolidone (PVP)). The maximum amount delivered into skin was 86.158 ± 7.82% of the initial GRB (2.1 mg) loaded on SMNs preparation. Pharmacokinetics study in rats indicated a dose-dependent profile of plasma GRB concentrations and that the controlled release of 2.1 mg dose was observed for 144 hours. In conclusion, these SMNs provided a potential minimally invasive route for controlled-release systemic delivery of poorly water-soluble drugs.